The Relationship of Feeding and Physical Activity Pattern With Primary Obesity In Children - Dedi Subardja; Suzy Irawati Sjahid; Nia Kania; Ponpon S Idjradinata (Media Gizi dan Keluarga, 2000)
Changes in lifestyle that influence food consumption and physical activity pattern tend to increase the prevalence of childhood obesity in Indonesia. The purpose of this study is to evaluate the relationship of dietary and physical activity pattern with the development of primary obesity in children. This study was conducted to 122 school age children in Bandung municipality from May to July 2000. Obesity status was determined by body mass index (BMI) and weight for height (W-H) classifications. Interview was done to assess the dietary pattern i.e habitual dietary pattern (HD) and 24-hour dietary record (DR) and daily physical activity pattern, i.e. physical activity score (PAS) and energy expenditure (EE). According to BMI classification, there are 81 obese and 41 non-obese children. While by W-H classification, the number of obese and non-obese children is 47 and 75. The study shows that obese children consume more calorie than non obese, and significant difference found in calorie intake based on DR between non obese and obese according to BMI (p=0.026) and W-H (p=0.001). Macro nutrient intake based on HD and RD does not differ significantly between obese and non obese children according to BMI and W-H (p>0.05). Based on HD and BMI degree of obesity, fat is the most in-fluencing macronutrient (F=3.392;p=0.006) but according to W-H, calorie has more effects (F=2.557;p=0.042). While by 24-hour DR in the BMI as well as W-H classifications carbohydrate intake was the most related macronutrient. No significant difference was found in micro nutrient intake except for calcium intake by DR according to W-H classification (p=0.043). Physical activity pattern reveals that obese children have lower PAS than non-obese (p=0.000) and a significant negative correlation with BMI (r=0,615;p